Antibiotic prescribing pattern in cesarean section - Nazrina, S; Chisty, S; Maruf, AA (Mediscope, 2016)
Use of antimicrobials in caesarean section has become an accepted practice to minimize the incidence of postoperative complications. Not many studies are available in Bangladesh regarding the using pattern of antibiotics in caesarean section. The objectives of the study was to find out the pattern of use of antibiotic prophylaxis in caesarean section and also the frequency of postoperative morbidity. The prospective cross-sectional study included 356 patients undergoing caesarean section in Prime Medical College Hospital, Rangpur and 10 different private clinics in Rangpur city. Patients demographics, perioperative data, antibiotic used with dosage and schedules were recorded. Investigations like pus, blood and urine culture and sensitivity were recorded for patients with postoperative complications. Change of antimicrobial following culture sensitivity report was noted. Most of the patients, 197 (55.3%), came from lower middle socioeconomic status. Major indication of cesarean section was emergency in 314 (88.2%) patients. The use of third generation cephalosporin (ceftriaxone) in majority of the patients, 209 (58.7%), was observed. Two drugs combination commonly included third generation cephalosporin and metronidazole, and in addition gentamicin was added when three drugs combination was used. Fifty five (15.5%) patients had postoperative complications which included fever, wound infection, urinary tract infection and endometritis. The mean duration (SD) of antibiotic administration was 12.4 (3.5) days in infected patients and 8.0 (2.1) days in non-infected patients, and the difference was statistically significant (p < 0.01). The mean duration (SD) of hospital stay was 15.4 (5.5) and 9.1 (3.9) days for infected and non-infected patients, respectively; and the difference was statistically significant (p < 0.01). Isolated micro-organisms from wound infection, urinary tract infection and lochia were gram-negative, and Escherichia coli, 16 (41.0%), was the common which was resistant to third generation cephalosporin and sensitive to amikacin. Obstetricians should utilize clinically effective antibiotics. Whenever possible, single drug rather than combination therapy should be used. Periodic surveillance of antimicrobial prophylaxis is essential to detect the emergence of antibiotic resistance. Mediscope Vol. 3, No. 1: January 2016, Pages 8-15